Respon Orang Tua terhadap Pebelajaran Daring di SMP Negeri 8 Kecamatan Kedurang Kabupaten Bengkulu Selatan - Hikmah Widya Yustika; Bahrin Bahrin (Universitas Dehasen Bengkulu, 2022)
This study aimed to determine the parents’response towardonline learningat SMP Negeri 8 Kedurang District, South Bengkulu Regency. This study used a descriptive research type with a qualitative approach. The data collection techniques of this study were observation, interview and documentation. The data analysis technique of this study used percentage analysis. The results of the study show that there were some parents' response toward online learning at SMP Negeri 8 Kedurang District, South Bengkulu Regency. It can proved with 17 respondents in terms of network availability 11.76% are in the no category. There are 17.65% in the category of few complaints, but seen 70.59% in the category of many complaints. Judging from the demand for internet quota turns out that there are still 11.76% in the always category, 17.65% in the sometimes category, but 70.59% is in the unfulfilled category. In terms of the implementation of online learning, 17.65% are in the easy category, 11.76% are in the less category, however, most of 70.59% are in the difficult category. In terms of providing facilities for online learning tools 5.89% are in the not burdensome category, 41.17% are in the somewhat burdensome category, but there are still 52.94% in the burdensome category.